Kesadaran Hukum Aparatur Pemerintahan Terhadap Kinerja Birokrasi di Sekretariat Daerah Kota Tidore Kepulauan - Muhammad Fazry (Jurnal Ilmiah Wahana Pendidikan, 2022)
Legal Awareness of Government Apparatus on Bureaucratic Performance at the Regional Secretariat of Tidore Islands City. Service is a very principle issue in the government system, therefore by providing excellent service to everyone it will have a positive impact in a government system. The forerunner to the birth of the Regional Autonomy Law was an effort to give authority to the regions in providing good services to the community in accordance with the needs of the people in their respective regions. gave birth to new powers and formed regional arrogance so that what was expected of excellent service turned into being served so that it was far from the expectations of the Act. The purpose of this study was to determine the level of legal awareness of local government apparatus in the era of regional autonomy in Tidore Islands City and to determine the performance of bureaucratic apparatus working in the regional secretariat of Tidore Islands City. The research method used is the Juridical Empirical method with a survey basis, namely conducting a test of the relationship between the characteristics that develop in certain populations. Thus this study was designed in qualitative research, namely in this study data were collected from respondents or samples that represented the population. Meanwhile, the survey is intended to be a deductive research approach by collecting extensive and in-depth information and explained in a deductive manner. That's why this research uses descriptive qualitative research. The output targets to be achieved are accredited national journals and proof of concepts or important characteristics analytically and experimentally that are feasible to be adopted and applied to this research.